Association of ESAT‐6/CFP‐10‐induced IFN‐γ, TNF‐α and IL‐10 with clinical tuberculosis: evidence from cohorts of pulmonary tuberculosis patients, household contacts and community controls in an endemic setting. (2nd May 2017) - Abebe, F.; Belay, M.; Legesse, M.; Mihret, A.; Franken, K. S.
Summary: Mycobacterium tuberculosis (Mtb) early secreted protein antigen 6 (ESAT‐6) and culture filtrate protein 10 (CFP‐10) are among candidate vaccines against tuberculosis (TB). Results of experimental animal models show that these antigens are associated with induction of strong T cell immunity [interferon (IFN)‐γ production], while others report that these proteins as virulent factors involved in pathogenicity of Mtb infection. However, the role of ESAT‐6/CFP‐10 during natural Mtb infections in humans has not been established. In this paper we present results of a longitudinal study from an Mtb ‐infected human population from an endemic setting. Whole blood assay was used to determine levels of IFN‐γ, tumour necrosis factor (TNF)‐α and interleukin (IL)‐10 against rESAT‐6/CFP‐10 in TB patients, household contacts and community controls. The levels of IFN‐γ, TNF‐α and IL‐10 against rESAT‐6/CFP‐10 at baseline were significantly higher in patients and community controls than in household contacts. In patients, no significant difference was observed in the level of these cytokines before and after chemotherapy whereas, in contacts, the level of these cytokines increased significantly and progressively over time. The study shows that the levels of IFN‐γ, TNF‐α and IL‐10 against rESAT‐6/CFP‐10 are depressed during Mtb infection or exposure but are elevated during clinical TB. Our findings from a study of naturally infected human population suggest that IFN‐γ, TNF‐α and IL‐10 against rESAT‐6/CFP‐10 are markers for clinical TB but not for protective immunity. Abstract : As part of a major project to investigate protective immune markers during Mycobacterium tuberculosis (Mtb) infection, levels of IFN‐γ, TNF‐α, and IL‐10 against recombinant ESAT‐6/CFP‐10 were measured in cohorts of pulmonary tuberculosis patients, household contacts and community controls in an endemic setting. Results of whole blood assay show that IFN‐γ, TNF‐α, and IL‐10 are associated with clinical tuberculosis but not with protective immunity. These results support earlier findings that ESAT‐6/CFP‐10 is a virulent factor involved in pathogenesis of Mtb infection, and raise an outstanding issue regarding the candidacy of ESAT‐6/CFP‐10 as effective vaccine against TB.